Antimicrobial resistance and clonality of Staphylococcus aureus causing bacteraemia in children admitted to the Manhiça District Hospital, Mozambique, over two decades - Garrine, Marcelino; Costa, Sofia Santos; Messa, Augusto; Massora, Sérgio; Vubil, Delfino; Ácacio, Sozinho; Nhampossa, Tacilta; Bassat, Quique; Mandomando, Inacio; Couto, Isabel (Frontiers in Microbiology, 2023)
Background Staphylococcus aureus is one of the main causes of bacteraemia, associated with high mortality, mainly due to the occurrence of multidrug resistant (MDR) strains. Data on antibiotic susceptibility and genetic lineages of bacteraemic S. aureus are still scarce in Mozambique. The study aims to describe the antibiotic susceptibility and clonality of S. aureus isolated from blood cultures of children admitted to the Manhiça District Hospital over two decades (2001–2019). Methods A total of 336 S. aureus isolates detected in blood cultures of children aged <5 years were analyzed for antibiotic susceptibility by disk diffusion or minimal inhibitory concentration, and for the presence of resistance determinants by PCR. The clonality was evaluated by SmaI-PFGE, spa typing, and MLST. The SCCmec element was characterized by SCCmec typing. Results Most S. aureus (94%, 317/336) were resistant to at least one class of antibiotics, and one quarter (25%) showed a MDR phenotype. High rates of resistance were detected to penicillin (90%) and tetracycline (48%); followed by erythromycin/clindamycin (25%/23%), and co-trimoxazole (11%), while resistance to methicillin (MRSA strains) or gentamicin was less frequent (≤5%). The phenotypic resistance to distinct antibiotics correlated well with the corresponding resistance determinants (Cohen’s κ test: 0.7–1.0). Molecular typing revealed highly diverse clones with predominance of CC5 (17%, 58/336) and CC8 (16%), followed by CC15 (11%) and CC1 (11%). The CC152, initially detected in 2001, re-emerged in 2010 and became predominant throughout the remaining surveillance period, while other CCs (CC1, CC5, CC8, CC15, CC25, CC80, and CC88) decreased over time. The 16 MRSA strains detected belonged to clones t064-ST612/CC8-SCCmecIVd (69%, 11/16), t008-ST8/CC8-SCCmecNT (25%, 4/16) and t5351-ST88/CC88-SCCmecIVa (6%, 1/16). Specific clonal lineages were associated with extended length of stay and high in-hospital mortality. Conclusion We document the circulation of diverse MDR S. aureus causing paediatric bacteraemia in Manhiça district, Mozambique, requiring a prompt recognition of S. aureus bacteraemia by drug resistant clones to allow more targeted clinical management of patients.